Production of Lutein-enriched Biomass by Growing Coccomyxa sp. (strain onubensis; Chlorophyta) under Spring Outdoor Conditions of Southwest Spain - Vaquero, Isabel; Ruiz-Domínguez, M. Carmen; Mogedas, Benito; Vílchez, Carlos; Vega, José M. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Coccomyxa sp. (strain onubensis) is an acidic environment microalga, which was grown under spring outdoor conditions of Huelva province (southwest, Spain). A 6 L pilot tubular photobioreactor was used to determine the influence of the environmental light and temperature conditions on the microalga growth and its intracellular content of carotenoids. Cloudy days supplied the adequate light intensity (maximum 1070 Î¼mol photons m-2 s-1) and temperature (maximum 32ºC) regimes for a biomass productivity of 0.28 g L-1 d-1 with an intracellular content of lutein (4.8 mg g-1 dry weight) and eventually Î²-carotene (0.8 mg g-1) obtained at the end of the day evening. This work supplies guidelines for a large-scale outdoor culture of Coccomyxa. sp. to supply lutein-enriched biomass, with the advantage of the growth at pH 2.5, which preserves cultures from contamination.